Veterinary Movement Control: An Online System During Covid-19 Pandemic - Razali, Fakhrulisham; Che Rose, Farid Zamani; Mohd Zain, Sharil Azwan; Azami, Mohammad Masrin (Journal of Social Transformation and Regional Development, 2022)
The Malaysian government led by Tan Sri Muhyiddin Yasin had announce the implementation the Movement Control Order (MCO) on 18th March 2020 due to the novel coronavirus (COVID-19) pandemic that has spread and killed thousands of people. This restriction was implemented to prevent the spread of the virus in this country. At the same time, the government needs to make sure that the food chain supply is available and delivered to people all over the country. To do that, some methods of approval and monitoring of the essential service provider are required. Besides the standard operating procedures, a clear workflow for this service needs to be provided to register and obtain approval prior to operation, which typically begins with manual forms. This paper will cover the transition from manual forms to an online automation system. This system has been used to replace the manual forms until the end of MCO restrictions.